Manipulating Genes and Brains: Bioethics and Law in the face of Human Enhancement - Morente Parra, Vanesa (2023)
This article analyzes the role of bioethics and law in the face of the development of meliorative intervention techniques on the genotype and the brain. With the development of the CRISPR/Cas9 technique in recent years, an individual could enhance his genetic conditions by manipulating his somatic cells. Similarly, with the new BCI techniques, an individual could connect his or her brain to an AI in order to stimulate and enhance certain brain areas. However, both bioethics and law seem to infer a general prohibition of meliorating interventions. What rational arguments support this prohibition? Is the human body an unavailable asset for the individual? Is individual freedom and autonomy unjustifiably limited by it?